Determination of 222Rn and 238U Concentrations in Some Selected Samples of Rock for Sulaimani Area (Kurdistan Region-Iraq) - Abdullah, Kamal O. (Sulaimani Journal for Pure and Applied Sciences, 2015)
Different rock samples collected from the Mountains located to the west and north of Sulaimani district. Solid state nuclear track detector technique, CR-39 passive detectors included, is used for analyzing concentrations Radon. The uranium concentrations determined from the secular equilibrium between uranium and radon activity. The concentrations of Radon and Uranium have been calculated. The maximum and the minimum concentrations determined (4774.524±17.665 and 224401.714) Bq/m3 for Radon and (0.313±0.143 ppm, 14.728±6.731 ppm) for uranium, respectively. The higher concentration values of both Byara (Mountain of Balkha) and Penjween is due to sample rocks formation compared to the values appeared from Ranya and Chaqchaq regions. The highest annual effective dose was 0.8μSv/hr, which is higher than the value 1mSv ~ 0.114 μSv/hr recommended by the International Commission on Radiological Protection ICRP..
Keywords: Rock; Radon; Uranium; SSNTD; CR39